Noma in a Pacient whitout Sistemic Involvement (Research, Society and Development, 2025)
Noma, also known as Cancrum oris or gangrenous stomatitis, is an infectious disease of bacterial origin, often in association with other microorganisms, affecting orofacial tissues and manifesting through a sequence of precursors. It begins as necrotizing gingivitis and progresses to necrotizing periodontitis and necrotizing stomatitis. In advanced stages, it can lead to facial mutilations, difficulty in eating, and psychological distress due to social stigma. Untreated, it can result in a mortality rate of up to 90%, mainly due to septicemia, dehydration, and malnutrition. When addressed early, the prognosis is favorable, and by treating its precursors, it is challenging to reach severe stages. The disease is often associated with children in impoverished social conditions, weakened immune systems, and malnutrition, especially in regions with low human development indices, such as sub-Saharan Africa, although some cases have been reported elsewhere. Treatment involves several phases, including debridement of necrotic areas, antibiotics, antimicrobial mouth rinses, and supportive periodontal therapy. Despite its rarity, infection can also occur in developed countries and affect adult patients, sometimes without underlying health conditions. The aim of this article is to report a clinical case of noma in a 31-year-old man, without systemic involvement, who sought treatment at the Maria Aparecida Pedrossian University Hospital in Campo Grande, Mato Grosso do Sul, Brazil, due to swelling in the submental region. After hospitalization, biofilm control and postoperative care, there was a satisfactory improvement in the clinical condition.